2015
DOI: 10.1007/s00464-015-4583-1
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of initial experience with single-incision robotic cholecystectomies (SIRC) demonstrating a high success rate in 465 cases

Abstract: Our large, multicenter study demonstrates that robotic single-site cholecystectomy is safe and feasible in a wide range of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…In a prospective study of RC, in a broadly inclusive patient population, Vidovszky et al [24] demonstrated that no bile duct injury occurred even with a body mass index of 30.1 AE 7.1 kg/m 2 . Another multicenter study of initial experience with RC [25] reported a rate of 0.4% of postoperative bile leakage. In a case-matched control study, Breitenstein et al [6] concluded that robotic-assisted cholecystectomy is safe and a valuable approach.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a prospective study of RC, in a broadly inclusive patient population, Vidovszky et al [24] demonstrated that no bile duct injury occurred even with a body mass index of 30.1 AE 7.1 kg/m 2 . Another multicenter study of initial experience with RC [25] reported a rate of 0.4% of postoperative bile leakage. In a case-matched control study, Breitenstein et al [6] concluded that robotic-assisted cholecystectomy is safe and a valuable approach.…”
Section: Discussionmentioning
confidence: 97%
“…Another multicenter study of initial experience with RC demonstrated a high success rate in 465 cases; Gonzalez et al. [25] reported a rate of 0.4% of postoperative bile leakage. In a case‐matched control study, Breitenstein et al.…”
Section: Discussionmentioning
confidence: 98%
“…9 However, that study was limited in that it did not include a comparative analysis for SIRC. In the present study, the operation time was 97.2 min, the console time was 49 min, and the docking time was 10 min, which is similar to other reports.…”
Section: Editorialmentioning
confidence: 99%
“…According to a previous report, there are limitations to this procedure, such as short-term follow up and selection bias. 9 Specifically, they found that the follow up period was too short to show the incisional hernia rate. Accordingly, additional studies investigating long-term outcomes are needed to establish the incisional hernia rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation